Code Mixing Analysis in the Movie Bulan Terbelah di Langit Amerika 2 - Halim, Nur Mutmainna; Warsidi, Warsidi; Efika, Siti Nurul; Halim, Abd (Vivid: Journal of Language and Literature, 2023)
This study aims: 1) to reveal types of code mixing that appeared in the Bulan Terbelah di Langit Amerika 2 movie and 2) to find out factors that cause code mixing in this movie. This study employed a descriptive qualitative method. In collecting data, this research applied note-taking as an instrument. To obtain data, the dialogues of the characters were analyzed thoroughly. Researchers implemented the theory of code-mixing by Muysken (2000) to find the types and the view of code-mixing factors from Hoffman (1991) for the analysis. The research results revealed three types of code mixing contained in this movie. They are insertion type (7 data or 29.17%), alternation type (12 data or 50%), and congruent lexicalization type (5 data or 20.83%). In addition, factors of code-mixing are also found in this movie. They are the lexical needs factor (9 data or 37.5%), emphasize something factor (3 data or 12.5%), talking about a particular topic factor (5 data or 20.83%), repetition used for clarification factor (2 data or 16.64%), soften or strengthen request or command factor (2 data or 8.33%, and expressing group identity factor (1 data or 4.16%). The most common form of code-mixing in this film is alternation when one language is used to fill in for another's lexical gaps throughout a conversation. They spoke in turn, and researchers found that a single sentence may be expressed in two languages with vastly different grammatical structures.